Solutions

 

1.

2H2(g) + O2(g) 2 H2O(g) + 2(242 kJ) DH = -484 kJ/mol

 

C(s) + O2(g) CO2(g) DH = -394 kJ/mol

 

CH4(g) + 75 kJ C(s) + 2 H2(g) DH = 75 kJ/mol

 

Sum:

 

CH4(g) + 2 O2(g) CO2(g) + 2 H2O(g) DH = -803 kJ/mole with sig figs: -8.0 X 102 kJ/mole

 

 

2. a. DH= + 74.8 kJ

DH= -110.5 kJ

 

Sum: + + 2 DH = -35.7 kJ

 

 

b. Calculate DH for

 

DH = 103.8 kJ

3C(s) + 3 O2(g) 3 CO2(g) DH = -393.5(3) kJ

4H2(g) + 2 O2(g) -->4 H2O(g) DH = -242(4) kJ

Sum : 3 DH = -2045 kJ with sig figs: -2.05 X 103 kJ/mole

 

 

 

3. 12 NH3(g) + 15O2(g) 12NO(g) + 18 H2O(l) DH = -293(12) kJ

12NO2(g) + 4H2O(l) 8 HNO3(aq) + 4 NO(g) DH = -45(12) kJ

 

12NO(g) + 6 O2(g) + 59 kJ 12 NO2(g) DH = + 59(12) kJ

 

Sum : 12 NH3(g) + 21 O2(g) 8 HNO3(aq) + 14 H2O(l) + 4 NO(g) DH = -3348 kJ with sig figs: -3.3 X 103 kJ/mole

 

 

4. 2NO (g) + 2*93 kJ N2(g) + O2(g) DH = 186 kJ

N2(g) + 2O2(g) 2 NO2 (g) DH = -34(2) kJ

 

Sum: 2 NO(g) + O2(g) 2 NO2(g) DH = 118kJ with sig figs: 1.2 X 102 kJ/mole

 

 

b. If you had used the data from #3, could you have gotten the same answer in one step? How?

Simply double the 3rd equation from that example: NO(g) + 0.5 O2(g) + 59 kJ NO2(g)

 

5.

Reaction

DH ( kJ )

 

2 B(s) + 1.5 O2(g) B2O3(s)

 

-1273

3H2(g) + 1.5 O2(g) 3H2O(l)

 

-286(3)

B2O3(s) + 3 H2O(g) B2H6(l) + 3 O2(g)

 

+2035

3H2O(l) ) 3H2O(g)

44 (3)

 

Sum: 2 B(s) + 3H2(g) B2H6(l) DH = 36 kJ